2013
DOI: 10.1016/j.jsat.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Minimum recommended physical activity, and perceived barriers and benefits of exercise in methadone maintained persons

Abstract: Methadone-maintained persons are at increased risk for many physical and mental health disorders compared to the general population. Increased physical activity could offset these risks. We assessed physical activity level, and perceived benefits and barriers to exercise in a group of 305 methadone-maintained smokers. Mean participant age was 39.9 years of age, 50.2% were male, 79.7% were non-Hispanic White, and mean body mass index was 29.8. Nearly 45% endorsed fair or poor physical health. Although participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 44 publications
0
38
0
2
Order By: Relevance
“…Most participants reported little or no past‐week moderate or vigorous physical activity, and thus appear to be inactive or sedentary . In the current study of individuals seeking MMT, a lower proportion (27%) met recommended weekly physical activity levels compared to a prior study of patients enrolled in MMT for at least 1 month . Differences in the patient population, measures used to measure physical activity, or treatment status at the time of assessment (newly enrolling or currently receiving MMT) may account for these differences.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Most participants reported little or no past‐week moderate or vigorous physical activity, and thus appear to be inactive or sedentary . In the current study of individuals seeking MMT, a lower proportion (27%) met recommended weekly physical activity levels compared to a prior study of patients enrolled in MMT for at least 1 month . Differences in the patient population, measures used to measure physical activity, or treatment status at the time of assessment (newly enrolling or currently receiving MMT) may account for these differences.…”
Section: Discussionmentioning
confidence: 56%
“…The promotion of exercise in MMT programs may be particularly timely because a recent study of methadone‐maintained participants found that the majority did not meet recommended weekly levels of physical activity . While exercise has been proposed as an intervention for enhacing the psychological functioning of patients in MMT and for managing pain in those with co‐occurring chronic pain and opioid use disorder, few studies have examined the feasibility, acceptability, or efficacy of these approaches .…”
Section: Introductionmentioning
confidence: 99%
“…Participants were 315 adult outpatient cigarette smokers recruited from nine MMTPs in the northeast U.S. for a smoking cessation study (Caviness et al, 2013a, 2013b). Eligibility criteria included: (1) being over 18 years of age; (2) being a current, regular smoker (at least 10 cigs/day for the past 3 months); (3) speaking English or Spanish; (4) having received methadone for at least the last month; (5) agreeing to be available for 12 months; and, (6) willingness to set a quit date seven days after the baseline assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this consensus, people with harmful substance use typically report far lower rates of exercise than the general population [8]. This is true for out-of-treatment users, inpatients [16,17], and outpatients [16], with mixed evidence from inmates [18,19]. Substance use disorders are the most common mental disorders among inmates, with pooled estimates of a 51% prevalence of drug use disorders worldwide, and a 24% prevalence of alcohol use disorder [20].…”
Section: Introductionmentioning
confidence: 99%